Social entrepreneur perceived success by integrating cognitive mapping and MCDA - Carvalho, E.; Bicho, M. (Journal of Management, Spirituality and Religion, 2023)
The dual nature of social enterprises (social and financial goals) brings crucial challenges regarding the tensions to which objectives address, and therefore success is harder to assess and attain. This study aims to respond to this gap of knowledge by investigating social enterprises perceived path to success. It gives voice to social entrepreneur’s notion of success and applies the combination of Cognitive Mapping and MACBETH, techniques that help to capture success criteria’s complexity. The outcome of this study is a framework that allows to understand the way social entrepreneurs perceive success for their social enterprises. The findings reveal five indicators, in which the most important is Financial Sustainability, followed by Social Impact, whereas Business Model is considered the least important factor.